Monitoring tren dan produktivitas hasil tangkapan kapal huhate yang berpangkalan di Pelabuhan Perikanan Samudera Bitung (Monitoring trend and productivity of pole and liner catch that based in Bitung Oceanic Fishing Port) - Resya I. Firmansyah; Emil Reppie; Vivanda O.J. Modaso (Universitas Sam Ratulangi, 2017)
Skipjack (Katsuwonus pelamis) belongs to a large pelagic fish, which is one of the leading commodity in North Sulawesi fishery sector. The fishing gear which is specifically intended for catching skipjack is pole and line; that has been used by fishermen of North Sulawesi before the second world war. But it does not have high competitiveness compared to other Asean countries, because the production process is not fully efficient yet. Therefore, this study aims to monitor the trend and productivity of pole and liner based in Bitung Oceanic Fishing Port (OFP) with used descriptive method; Secondary data was collected by recording information at Bitung OFP and related institutions, in the form of catch data, statistical reports and annual reports, as well as relevant literature review. Trend of pole and liner catch were analyzed by linear trend method through least square approach; While the productivity of the vessel is analyzed by comparing the catch and tonnage of the vessel. The main target of pole and liner is skipjack, but caught also yellowfin tuna and other species; with total catches ranging from 3,730.46 tons to 14,253.98 tons per year; and there are increasing trend. Estimated production of skipjack that will be landed at Bitung OFP in 2017 is amounted to 6,988.49 tons and yellowfin tuna 2,188.76 tons. While skipjack in 2018 amounted to 8,475.89 tons and yellowfin tuna of 2861.58 tons.Pole and liner are considered productive on average per year by 62% while the unproductive at 38%.Keywords: Pole and liner, Monitoring Trend and Productivity, skipjack, yellowfin tunaABSTRAKIkan cakalang (Katsuwonus pelamis) tergolong ikan pelagis besar, yang merupakan salah satu komoditi unggulan di sektor perikanan Sulawesi Utara. Alat tangkap yang digunakan untuk menangkap ikan cakalang adalah huhate; telah digunakan oleh nelayan Sulawesi Utara sebelum perang dunia kedua. Namun belum memiliki daya saing yang tinggi dibandingkan dengan negara Asean lainnya, karena proses produksi belum sepenuhnya efisien. Penelitian ini bertujuan untuk memonitoring trend dan produktivitas kapal huhate yang berpangkalan di Pelabuhan Perikanan Samudera (PPS) Bitung dengan menggunakan metode deskriptif; data sekunder dikumpulkan dengan cara mencatat informasi di PPS Bitung dan instansi terkait, berupa data hasil tangkapan, laporan statistik dan laporan tahunan, serta telaah pustaka yang relevan. Tren tangkapan kapal huhate dianalisis dengan metode tren linier melalui pendekatan least square; sedangkan produktivitas kapal dianalisis dengan membandingkan hasil tangkapan dan tonase kapal Target utama kapal huhate adalah ikan cakalang, tetapi tertangkap juga madidihang dan jenis lain; dengan jumlah tangkapan berkisar antara 3.730,46 ton - 14.253,98 ton per tahun; dan kecenderungan meningkat. Perkiraan produksi cakalang yang akan didaratkan di PPS Bitung untuk tahun 2017 adalah sebesar 6.988,49 ton dan madidihang 2.188,76 ton. Sedangkan cakalang untuk 2018 sebesar 8.475,89 ton dan madidihang sebesar 2.861,58 ton.Kapal huhate yang dinilai produktif, rata-rata per tahun sebesar 62% sedangkan yang tidak produktif sebesar 38%.Kata kunci: Kapal huhate, Monitoring Tren dan Produktivitas, Cakalang, Madidihang